Pengaruh Struktur Modal, Pertumbuhan Laba, Ukuran Perusahaan Dan Likuiditas Terhadap Kualitas Laba Pada Perusahaan Manufaktur Sektor Industri Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2018-2021 - Anis Magfiroh; Listyorini Wahyu Widati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Good profit quality reflects sustainable future earnings and represents the true financial performance of the company. This research aims to evaluate and study the impact of capital structure, profit growth, company size, and liquidity on profit quality in consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2021. The method used to select the sample is purposive sampling. A total of 35 consumer goods companies were chosen according to predetermined sample criteria. Multiple linear regression analysis was used to analyze the data and processed using IBM SPSS Statistics 22 software. The research results indicate that capital structure has a negative but insignificant impact on profit quality. Profit growth and company size have a positive but insignificant impact on profit quality. Additionally, liquidity has a negative and significant impact on profit quality. Keywords : Capital Structure, Profit Growth, Company Size, Liquidity, Earnings Quality